2018
DOI: 10.30682/nm1803h
|View full text |Cite
|
Sign up to set email alerts
|

Price Volatility Transmission Among Cereal Markets. The Evidences for Turkey

Abstract: The purpose of this study is to examine the price volatilities in corn, wheat and barley markets in Turkey, and to analyze the volatility transmission across the prices of these commodities. The Baba-Engle-Kraft-Kroner (BEKK) version of the multivariate Generalized Autoregressive Heteroskedastic (MGARCH) method was used to evaluate the conditional correlations and the time variation of the volatilities of the prices of the selected products on a monthly basis. The analysis period covers the timeframe between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Barely is a vital agricultural input in livestock production; in fact, more than 90 percent of barley production and import utilized as a livestock production input and role of this input remained sustainable in the last decade (Mashayekhi et al, 2005;WFP, 2016). Because of the important role of barely in livestock feed market and a considerable share of international trade in providing this input, price volatility in the price of this input in the International market might be transmitted to livestock markets and the producers and consumers welfare will affect (Cinar, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barely is a vital agricultural input in livestock production; in fact, more than 90 percent of barley production and import utilized as a livestock production input and role of this input remained sustainable in the last decade (Mashayekhi et al, 2005;WFP, 2016). Because of the important role of barely in livestock feed market and a considerable share of international trade in providing this input, price volatility in the price of this input in the International market might be transmitted to livestock markets and the producers and consumers welfare will affect (Cinar, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Moreover, a price monitoring system should designed in order to inform the government about the global price movement and volatility to modify the trading strategy based on the different situation. Finally, Cinar (2018) recommended that the government should be designed a livestock and agricultural policy as a whole; however, where domestic markets are heavily dependent on international markets, agricultural, livestock, and trade policy should be designed as a whole.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Specifically, energy prices, monetary policy, speculative activities, sudden trade restrictions and lack of information are the important determinants of price volatility in agricultural markets. Cinar (2018) used the BEKK-MGARCH 2 model to test the interdependence between volatility movements and transmissions in grain prices between January 2003 and August 2017. The results confirmed one-way price volatility transmission from corn and barley to the wheat market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although causality ran both ways, this suggested that much policy intervention in response to shocks to Ukraine's wheat and flour markets might have increased rather than reduced instability. Cinar (2018) 2019) analyzed vertical price transmission in two typical Italian wheat chains, the pasta and bread chains. The authors detected the evidence of asymmetric price transmission having applied a co-integration methodology.…”
Section: Introductionmentioning
confidence: 99%